Monetary Policy and Economic Change - Whittlesey, C. R. (The Review of Economics and Statistics, 1957)
The description of politics as art of the applies likewise to public policy in general and to monetary policy in particular. To say that central banking is an art rather than a science, as both students and practitioners of central banking have been accustomed to do, is not to deny that, in this as in every other branch of applied economics, scientific methods and a scientific attitude can be extraordinarily fruitful. But the fact does remain that central banking is an art. The principal weakness of central bankers lies not in any failure to recognize that fact but in deciding what constitutes the possible when it comes to the application of their art. The main difficulty confronting central bankers is that what is possible for central bank policy is in no sense an absolute. It is not that what is possible is merely a matter of expediency, although expediency undoubtedly has to be considered; the policy-maker who disregards what is realistic is only a little less ridiculous than the one who forgets what is ideal.' The more baffling consideration is that what it is possible for central banking to accomplish, and by what means, is relative to many things. These include such internal considerations as the objectives to which it is committed, the guides available to it, the instruments at its disposal. They also include such outside factors as the state of the economy, the international climate both political and economic, and the attitude of the public. While some of these endogenous and exogenous elements are subject to accurate determination or control, others clearly are not. To suggest that the problem of the practitioners of the art of central banking is difficult is not to imply that they do as good a job as can legitimately be asked. A better job can be expected, however, only through heightened sensitivity to the changing environment in which central bankers operate and increased willingness to modify central bank actions in the light of these changes. And it is highly probable that the pressure to effect these adaptations will have to come mainly from students of the art who are outside the system itself.2